Comparative growth of 11 year old Acacia aulacocarpa A. CUNN. EX Benth from four provenances. - Senin, Abdul Latib; Abdul Hamid, Hazandy; Kusno, Mohd Ashadie; Abdu, Arifin; Ismail, M. K. (Academic Journals, 2011)
The aim of this study was to evaluate the growth potential of Acacia aulacocarpa A. Cunn. Ex Benth in four provenances of Malaysia. A field trial was established in Kampung Aur Gading, Kuala Lipis and Pahang using a Completely Randomized Block Design (RCBD) with four replications. The seeds used were from the Papua New Guinea and Queensland regions. Survival, total height and diameter at breast height (dbh) were assessed. There were significant differences at p<0.05 found between regions and provenances for survival, height and dbh. Arufi East Morehead WP (PNG) and West Morehead (PNG) provenances perform better than the ones from Queensland region.